Metrics for green analytical chemistry. Issue 15 (15th March 2016) - Tobiszewski, Marek
Abstract : Green analytical chemistry although is not a new concept, it does not have greenness metrics system. Some efforts have been made to develop suitable metrics for analytical chemistry. The present review analyses the different methods proposed for an accurate greenness metrics system. Abstract : Green analytical chemistry, although not being a new concept, does not have a greenness metrics system. Green chemistry metrics are not suitable for analytical procedure assessment because they often refer to the mass of the product. Some efforts have been made to develop suitable metrics for analytical chemistry. Some are simple to use but do not cover all aspects of analytical methods' environmental impact. Others are more comprehensive but may be difficult to be applied. The analytical reagents were not assessed but some clues about their greenness can be obtained from assessments from other branches of chemistry. New reagents and solvents applied in analytical chemistry require their detailed assessment in terms of greenness. Environmental issues have to be taken into consideration during reagent and solvent selection, analytical waste disposal practices, the energetic requirements of analytical processes and the development or selection of analytical procedures, and, for that reason, metrics systems are required.